Association between Educational Environment in Kindergarten and Executive Functions in Preschool Age - Belolutskaya A.K; Veraksa A.N; Almazova O.V; Bukhalenkova D.A; Gavrilova M.N; Shiyan I.B (Moscow State University of Psychology and Education, 2019)
This paper presents an empirical study on the interrelationship between levels of regulatory functions development in preschool children and the quality of preschool education.The study involved 31 groups of preschool children in Moscow (657 children aged 5-6 years).ECERS-R scales and the NEPSY-II battery were used.A number of significant correlations was revealed between such components of regulatory functions as verbal working memory, visual-spatial working memory, inhibitory control, cognitive flexibility and various environmental factors.The paper stresses the importance of creating conditions for recreation and relaxation as well as for the development of gross motor skills, and highlights the significance of group interaction for the development of regulatory functions in children.